Challenges and opportunities for software change request repositories: a systematic mapping study. Issue 7 (16th December 2013) - Cavalcanti, Yguaratã Cerqueira; da Mota Silveira Neto, Paulo Anselmo; Machado, Ivan do Carmo; Vale, Tassio Ferreira; de Almeida, Eduardo Santana; Meira, Silvio Romero de Lemos
ABSTRACT Software maintenance starts as soon as the first artifacts are delivered and is essential for the success of the software. However, keeping maintenance activities and their related artifacts on track comes at a high cost. In this respect, change request (CR) repositories are fundamental in software maintenance. They facilitate the management of CRs and are also the central point to coordinate activities and communication among stakeholders. However, the benefits of CR repositories do not come without issues, and commonly occurring ones should be dealt with, such as the following: duplicate CRs, the large number of CRs to assign, or poorly described CRs. Such issues have led researchers to an increased interest in investigating CR repositories, by considering different aspects of software development and CR management. In this paper, we performed a systematic mapping study to characterize this research field. We analyzed 142 studies, which we classified in two ways. First, we classified the studies into different topics and grouped them into two dimensions: challenges and opportunities. Second, the challenge topics were classified in accordance with an existing taxonomy for information retrieval models. In addition, we investigated tools and services for CR management, to understand whether and how they addressed the topics identified. Copyright © 2013 John Wiley & Sons, Ltd.